Віра як складник релігійного навернення Аврелія Августина - Соломаха, І. Г.; Solomaha, I. G. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано питання щодо виникнення, формування та значущості релігійної віри як фено-мену процесу релігійного навернення Аврелія Августина; досліджено її зв’язок із любов’ю, надією, від яких залежить її ступінь глибини. Віра й розум взаємно доповнюють одне одного, що виражається в тезі «вірую, щоб розуміти». За інтерпретацією Августина, кожна із чеснот – віра, надія, любов – є лише вираженням любові до Бога. The paper analyzes the issues of emergence, forming and significance of religious faith as a phenomenon of the process of religious conversion of St. Augustine, investigates its relationship with love and hope, which determine its degree of depth. For Augustine, God as creator of the world, absolute Good, Beauty, Perfection is a major factor in the formation of religious belief. It is emphasized that personal belief constructs «I-person» only in the process of being involved in the Absolute, that is God, because «I» exist only when there is a God in me. It is noted that the process of self-knowledge should be combined with the knowledge of God, in which faith plays a significant role. The author states that Augustine’s faith is determined by his personal religious experience rather feat conversion to Christ. Faith and reason are mutually complementary and that expressed in thesis: «I believe in order to understand». In Augustineʼs interpretation of each of the virtues – faith, hope, love – contribute to the spiritual quest that led him to the adoption of the Christian worldview.
Faith as a Component of Religious Conversion of St. Augustine
Keywords: релігійна віра; релігійна віра; релігійна віра; the process of conversion; Аврелій Августин; Aurelius Augustine; Бог; God; надія; hope; любов; love